2005
DOI: 10.1158/0008-5472.can-05-2119
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Induced Down-regulation of BRCA1 Expression by E2Fs

Abstract: Decreased BRCA1 expression in the absence of genetic mutation is observed frequently in sporadic cancers of the breast and other sites, although little is known regarding the mechanisms by which the expression of this gene can be repressed. Here, we show that activating and repressive E2Fs simultaneously bind the BRCA1 promoter at two adjacent E2F sites in vivo, and that hypoxia induces a dynamic redistribution of promoter occupancy by these factors resulting in the transcriptional repression of BRCA1 expressi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
321
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 314 publications
(344 citation statements)
references
References 47 publications
14
321
2
1
Order By: Relevance
“…Moreover, since hypoxia decreases BRCA1 expression (Bindra et al, 2005), we further investigated the effects of normoxia and hypoxia on CYP1A1 and BRCA1 protein expression in ZR-75 cells (Figs. 5B and 5C).…”
Section: Results Inmentioning
confidence: 99%
“…Moreover, since hypoxia decreases BRCA1 expression (Bindra et al, 2005), we further investigated the effects of normoxia and hypoxia on CYP1A1 and BRCA1 protein expression in ZR-75 cells (Figs. 5B and 5C).…”
Section: Results Inmentioning
confidence: 99%
“…Hypoxic tumor cells exist in colorectal cancer, and the level of hypoxia is prognostic for clinical outcome (10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Hypoxia may give rise to genetic instability by downregulating multiple DNA repair pathways, including the DNA mismatch repair (MMR) and homologous recombination (HR) pathways (20)(21)(22)(23)(24)(25)(26)(27). For example, Chan and colleagues demonstrated an alternate mechanism of translational inhibition of the HR proteins RAD51 and BRCA2 (23).…”
Section: Introductionmentioning
confidence: 99%
“…A model of acute hypoxia-induced transcriptional repression has been proposed by Bindra et al (23,26) who showed that the hypoxic down-regulation of RAD51 and BRCA1 can be mediated by altered E2F transcriptional activation and repression. In other cell lines, the RNA and protein expression of HR genes is discordant after chronic hypoxic exposure (25), suggesting an additional level of genetic control.…”
Section: Introductionmentioning
confidence: 99%